Urgensi Pengaturan Laporan Dana Kampanye Dalam Penyelenggaraan Pemilu Serentak di Indonesia - Al Fatah Hidayat (Fakultas Hukum Universitas Islam Indonesia, 2023)
The flow of campaign fund donations is often a source of misappropriation and even creates the potential for money politics. For this reason, the General Election Commission (KPU) as an independent institution authorized to carry out elections forms regulations related to campaign finance reporting. There are three forms of campaign fund reports regulated by the KPU, namely; LADK, LPSDK and LPPDK. Therefore, there are several things that become the focus of this research, namely; the urgency of regulating campaign finance reports in organizing simultaneous elections in Indonesia and the legality of arrangements related to reports on the receipt of campaign donations in simultaneous elections in Indonesia. This research uses doctrinal legal research with a juridical-normative approach. Regulations related to campaign finance reports are important considering that campaigns are often tainted with various kinds of corrupt practices. The normative basis of the Law related to LPSDK is not explicitly stated. LPSDK can be interpreted as a constitutional convention as well as beleidsregel.